Radiocarbon, Tephra, and Paleomagnetic Data from 5 Northern North Atlantic Sediment Cores to support Reilly et al. 2023, "The Amplitude and Timescales of 0-15 ka Paleomagnetic Secular Variation in the Northern North Atlantic." - Reilly, Brendan; Stoner, Joseph; Ólafsdóttir, Sædís; Jennings, Anne; Hatfield, Robert; Kristjánsdóttir, Gréta Björk; Geirsdóttir, Áslaug (Zenodo, 2023)
Data in support of Reilly et al., 2023, "The Amplitude and Timescales of 0-15 ka Paleomagnetic Secular Variation in the Northern North Atlantic." Published in the Journal of Geophysical Research: Solid Earth. Excel file includes worksheets for the following data: Tabular versions of the Supplementary Data Tables from the associated publication: Supplementary Table S1 from Publication: 14C data from sediment cores used in study Supplementary Table S2 from Publication: 14C data used in the GREENICE15 Stack Supplementary Table S3 from Publication: Tephra data used in study Paleomagnetic Datasets for the Characteristic Remanent Magnetizations used in this study: Paleomagnetic Data for Core MD99-2264 Paleomagnetic Data for Core MD99-2265 Paleomagnetic Data for Core MD99-2266 Paleomagnetic Data for Core MD99-2269 Paleomagnetic Data for Core MD99-2322 Independent radiocarbon based Age Models for 5 cores used in this study: Independent Age Model for Core MD99-2264 Independent Age Model for Core MD99-2265 Independent Age Model for Core MD99-2266 Independent Age Model for Core MD99-2269 Independent Age Model for Core MD99-2322 PSV Dynamic Time Warping (DTW) solutions of 3 cores to target curve, as described in publication DTW solution for MD99-2265to target curve DTW solution for MD99-2266to target curve DTW solution for MD99-2322to target curve GREENICE15 PSV Stack Age model for GREENICE15 Stack using combined radiocarbon dates and correlated equivalent depth scale Inclination, Declination, and alpha 95 for the GREENICE15 PSV Stack This work was supported by National Science Foundation awards EAR-1645411 and OCE-2300114.